Synthesis of some acetophenone (per-O-acetyl-β-maltosyl)-thiosemicarbazones - Thanh, Nguyen Dinh; Van, Hoang Thi Kim; Ha, Nguyen Hai; Giang, Do Thi Thuy (Vietnam Journal of Chemistry, 2012)
A series of per-O-acetyl-b-D-glycosyl thiosemicarbazones of acetophenones were obtained from reaction of per-O-acetyl-b-D-glycosyl isothiocyanates with corresponding acetophenones in ethanol or acetic acid as solvent using microwave-assisted. Structures of thiosemicarbazones were confirmed by spectroscopic methods.